(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The importance of engineering education in promoting engineering students’ entrepreneurial attitudes and behaviours now is widely recognised. The aim of the research is to explore international engineering Master students’ views on digital entrepreneurship in a host European country underpinning the elaboration of implications for engineering education in a host country. The research methods imply the use of both - theoretical and empirical - methods. Theoretical methods included analysis of scientific literature, theoretical modelling, systematisation, synthesis, comparison, generalisation. The empirical study was carried out in Germany in February 2021. 32 engineering Master students took part in the online survey. The online survey was based on the online questionnaire. The obtained data were described with the use of percentage, standard deviation and weighted average. The data description was followed by data interpretation and summarization. The use of the theoretical methods allows identifying that digital entrepreneurship is a supplement to traditional settings entrepreneurship proceeds in. The theoretical research resulted in the conceptual framework built of engineering student’s intention to become a digital entrepreneur, the use of the host country language, the use of engineering knowledge in digital entrepreneurship. The results of the empirical study allow finding out that the engineering Master students’ view digital entrepreneurship in a positive way. The survey results show that the engineering students focus their digital entrepreneurship on their professional field, namely engineering. The survey also outlined two major factors, namely host country language and host country rules, that limit the opportunities of becoming a digital entrepreneur in a host country. The implications for engineering education, that international engineering Master students receive in a host country, imply the integration of entrepreneurial culture, namely host country language and host country rules, into engineering education in a host country. The emphasis of the host country language and host country rules should be placed on their use for entrepreneurial purposes. By the entrepreneurial purposes, specific activities that are tied to entrepreneurship are meant. Training of host country language and host country rules within engineering education should be centred on their use for entrepreneurship.